PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS FLIPBOOK PADA CAPAIAN PEMBELAJARAN ANATOMI FISIOLOGI RAMBUT UNTUK KELAS X TKKR SMKN 1 POGALAN TRENGGALEK - Risky Fatimah Azzahro; Dewi Lutfiati; Dindy Sinta Megasari; Sri Usodoningtyas (Jurnal Tata Rias, 2025)
Indonesia Inggris 1.450 / 5.000 The development of technology encourages the development of flexible digital learning media, one of which is the use of flipbooks which are increasingly used. This study aims to determine the feasibility of the media, interest in learning using the media and learning outcomes after using the media. This research approach uses R&D (Research and Development) Borg and Gall with reference to 8 stages, namely: 1) Potential and problems; 2) Data collection; 3) Product design; 4) Design validation; 5) Design revision; 6) Product trial; 7) Product revision; 8) Usage trial. This study was conducted with a small group trial of 15 students of class XI TKKR 2 and 30 students of class X TKKR 1 in media on a class scale. The results of the media feasibility evaluation showed that the average final score reached 4.46, which indicated that the learning media was classified as effective and feasible to use in the teaching and learning process. The learning interest of the participants is categorized as very good with a percentage of 97% and the average learning outcomes of students after using interactive learning media based on flipbooks on learning outcomes of hair anatomy and physiology obtained significant results of 0.000 <0.05, thus, the average achievement of student learning outcomes, namely 84.6, experienced a significant increase, exceeding the figure of 75 according to the school KKTP standard after the implementation of interactive learning media based on flipbooks.